Transnasal humidified rapid-insufflation ventilator exchange compared with laryngeal mask airway for endoscopic thoracic sympathectomy: a randomized controlled trial - Lin, Chunmei; Wang, Dandan; Yan, Yulu; Zhong, Ruihan; Li, Chaoyang; Zhang, Jie (Frontiers in Medicine, 2023)
Background Transnasal humidified rapid-insufflation ventilator exchange (THRIVE) has the characteristics of operating easily and maintaining oxygenation and eliminating CO2, which makes it possible to be used in endoscopic thoracic sympathectomy (ETS). The application of THRIVE in ETS remains undefined. The purpose of this randomized controlled study is to assess the efficacy between THRIVE and laryngeal mask airway (LMA) for ETS. Methods In total, 34 patients from May 2022 to May 2023 in Huazhong University of Science and Technology Union Shenzhen Hospital undergoing ETS were randomly divided into a THRIVE group (n = 17) and an LMA group (n = 17). A serial arterial blood gas analysis was conducted during the perioperative period. The primary outcome was the arterial partial pressure of carbon dioxide (PaCO2) during the perioperative period. The secondary outcome was arterial partial pressure of oxygen (PaO2) during the perioperative period. Results The mean (SD) highest PaCO2 in the THRIVE group and LMA group were 99.0 (9.0) mmHg and 51.7 (5.2) mmHg, respectively (p < 0.001). The median (inter-quartile range) time to PaCO2 ≥ 60 mmHg in the THRIVE group was 26.0 min (23.2–28.8). The mean (SD) PaO2 was 268.8 (89.0) mmHg in the THRIVE group and 209.8 (55.8) mmHg in the LMA group during surgery (p = 0.027). Conclusion CO2 accumulation in the THRIVE group was higher than that of the LMA group during ETS, but THRIVE exhibited greater oxygenation capability compared to LMA. We preliminarily testified that THRIVE would be a feasible non-intubated ventilation technique during ETS under monitoring PaCO2.